Javni prostor in podoba mesta - Nikšič, Matej (Urbani izziv, 2003)
Physical limits of public urban spaces (morphological aspect) have an important role in the design of city image. It is not only the form; the process of visual perception that is established with the presence of the observer, is also important. The theme is dealt with by morphological and visual approaches. The first focus on research of physical form, the second try to explain, how a viewer perceives physical form and understands it.
Keywords: architecture; arhitektura; arhitekturni prostor; Melle Stomp; mesto; morfologija; prostorski razvoj; urejanje prostora; vizualna forma